Rethinking Perceived Quality Through The Lens of Entrepreneurial Marketing: Pathways To Customer Delight - Bramantyo, Paskalis Dio; Herdinata, Christian; Sembiring, Murpin; Utami, Christina Whidya; Dewi, Liliana (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Entrepreneurial Marketing (EM), which blends entrepreneurship with marketing principles, is crucial in Indonesia’s competitive mobile phone industry. Perceived quality and customer satisfaction are key success indicators, yet the role of gender differences remains underexplored.Purpose: First, it identifies the entrepreneurial marketing factors influencing perceived quality and customer satisfaction among Indonesian mobile phone users. These factors include performance, reliability, conformance, serviceability, durability, assurance, perceived price, product attributes, branding, and corporate image. Second, it analyzes whether satisfaction levels differ between male and female customers. Design/methodology/approach: This study applied a quantitative research design with survey data gathered from mobile phone users in Jakarta, Bandung, Surabaya, Medan, Semarang, Yogyakarta, Surakarta, and Makassar. These cities represented diverse demographic and economic contexts. A structured questionnaire measured ten factors of perceived service quality, and canonical discriminant analysis was used to test gender-based differences in satisfaction. Findings: The findings provide fresh insights for business professionals. Male and female customers share similar perceptions regarding many aspects of service quality. However, the study highlights that assurance and after-sales services, such as warranty, repair time, and spare parts, are more important for female customers. It indicates the need for firms to design strategies that recognize gender-specific priorities. Notably, the study confirms that female customers represent an equally vital market segment, challenging conventional practices that often prioritize men in marketing approaches.Conclusion: Perceived service quality significantly impacts customer satisfaction within entrepreneurial marketing. Differences in perception and satisfaction levels between male and female customers indicate that gender is crucial in shaping service experiences and evaluations. The ten dimensions of service quality analyzed succeeded in providing a comprehensive overview of the important elements that affect customer satisfaction of mobile phone users in various major cities in Indonesia. Originality/value: This research contributes to entrepreneurial marketing literature by adopting a gender-based lens to analyze customer satisfaction in the Indonesian mobile phone sector. The application of canonical discriminant analysis adds methodological novelty, enabling the detection of subtle but relevant gender differences. The study provides actionable guidance for practitioners designing inclusive marketing campaigns that value male and female customers equally. It offers academics a foundation for extending gender-based EM studies into other industries and cultural settings, bridging theory with practice. Keywords: entrepreneurial marketing, customer satisfaction, perceived quality, gender delight, phone industry